2021
DOI: 10.1007/s12325-021-01971-9
|View full text |Cite
|
Sign up to set email alerts
|

Fixed-dose Combination of Metoprolol, Telmisartan, and Chlorthalidone for Essential Hypertension in Adults with Stable Coronary Artery Disease: Phase III Study

Abstract: Introduction:The aim of the study was to evaluate the efficacy and safety of fixed-dose combination (FDC) of metoprolol, telmisartan, and chlorthalidone in patients with essential hypertension and stable coronary artery disease (CAD) who showed inadequate response to dual therapy.Methods: In this phase III, open-label, multicenter study, 254 adults with stable CAD having uncontrolled hypertension despite being treated with FDC of metoprolol (25/50 mg) and telmisartan (40 mg) were included. Patients received ei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…Most of the studies regarding combination therapy prefer lower dose of chlorthalidone as 3.125-12.5 mg combination in dual 25 or triple therapy. [26][27][28][29] Safety results of our study regarding triple combination therapy including chlorthalidone 25 mg showed that treatment emergent adverse event occurred in 30(15.6%) patients in TEL/AML/CHTD group and 18 (9.5%) patients in TEL/AML group. Treatment related adverse events occurred in 20(10.4%) patients of TEL/AML/CHTD group and 10(5.3%) patients of TEL/AML group.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Most of the studies regarding combination therapy prefer lower dose of chlorthalidone as 3.125-12.5 mg combination in dual 25 or triple therapy. [26][27][28][29] Safety results of our study regarding triple combination therapy including chlorthalidone 25 mg showed that treatment emergent adverse event occurred in 30(15.6%) patients in TEL/AML/CHTD group and 18 (9.5%) patients in TEL/AML group. Treatment related adverse events occurred in 20(10.4%) patients of TEL/AML/CHTD group and 10(5.3%) patients of TEL/AML group.…”
Section: Discussionmentioning
confidence: 74%
“…Most of the studies regarding combination therapy prefer lower dose of chlorthalidone as 3.125–12.5 mg combination in dual 25 or triple therapy. 26 , 27 , 28 , 29 …”
Section: Discussionmentioning
confidence: 99%
“…Thus, CAD and arterial hypertension [ 76 , 77 , 78 , 79 , 80 , 81 ], CAD and atrial fibrillation [ 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 ] and CAD and vascular cognitive disorders [ 92 , 93 , 94 , 95 ] are common comorbid conditions with overlap syndrome. Therefore, the study of LTL seems important not only in isolated CAD and AMI but also in these syndromes of mutual aggravation.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, this trend could be clarified by new, large, and multicenter studies with a similar design in the future. Thus, CAD and arterial hypertension [76][77][78][79][80][81], CAD and atrial fibrillation [82][83][84][85][86][87][88][89][90][91] and CAD and vascular cognitive disorders [92][93][94][95] are common comorbid conditions with overlap syndrome. Therefore, the study of LTL seems important not only in isolated CAD and AMI but also in these syndromes of mutual aggravation.…”
Section: Discussionmentioning
confidence: 99%